2015
DOI: 10.1186/s12940-015-0016-9
|View full text |Cite
|
Sign up to set email alerts
|

Mercury and psychosocial stress exposure interact to predict maternal diurnal cortisol during pregnancy

Abstract: BackgroundDisrupted maternal prenatal cortisol production influences offspring development. Factors influencing the hypothalamic-pituitary-adrenal axis include social (e.g., stressful life events) and physical/chemical (e.g., toxic metals) pollutants. Mercury (Hg) is a common contaminant of fish and exposure is widespread in the US. No prior study has examined the joint associations of stress and mercury with maternal cortisol profiles in pregnancy.ObjectivesTo investigate potential synergistic influences of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 53 publications
2
10
0
Order By: Relevance
“…Studies have shown that chronic stress can affect the body’s homeostasis, such as by interfering with the synthesis and secretion of adrenal GCs 40 , and chronic stress has a long-term impact on the activity of the HPA axis 41 . Additionally, chronic stress can seriously affect the body’s endocrine and metabolic balance, increasing susceptibility to a variety of diseases, including cardiovascular disease and type 2 diabetes 42 44 .…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that chronic stress can affect the body’s homeostasis, such as by interfering with the synthesis and secretion of adrenal GCs 40 , and chronic stress has a long-term impact on the activity of the HPA axis 41 . Additionally, chronic stress can seriously affect the body’s endocrine and metabolic balance, increasing susceptibility to a variety of diseases, including cardiovascular disease and type 2 diabetes 42 44 .…”
Section: Discussionmentioning
confidence: 99%
“…We generated an additive score that ranged from 0 to 11 which summarized the number of domains with at least one negative life events (NLE). Higher scores indicate greater psychosocial stress: a larger number of domains with negative life events reported indicates a greater diversity of stress experienced by a woman, which is more likely to overwhelm her coping resources (Schreier et al 2015). …”
Section: Methodsmentioning
confidence: 99%
“…There is accumulating evidence that combined exposure to chemical and non-chemical stressors has a synergistic effect on maternal and child health [10][11][12]. A significant negative effect on the maternal cortisol slope was found in pregnant women exposed to high stress and mercury levels above the median as compared with women experiencing high stress levels but mercury levels below the median [10]. In addition, a recent review portrayed the synergistic effect of air pollution and stress during pregnancy on child outcomes, especially asthma and wheezing [12].…”
Section: Introductionmentioning
confidence: 99%